(untitled) (Journal of Forensic Medicine & Toxicology, 2018)
Isotopes have been extensively utilized in diverse scientific fields like geology, ecology, hydrology, wildlife forensics, food industry, forensic anthropology and archaeology, geographical, pharmacological and medical research for different purposes. Stable isotope analysis of the evidentiary material/s found in forensic and bioarchaeological contexts is gaining more and more importance these days around the globe. This biogeochemical tool has been increasingly used in biological profiling of unknown human skeletal remains as to their geographic origin, migration patterns before or around death, dietary habits, pathological and physiological stress status, drug origin, processing and its trafficking routes etc. It is comparatively a cost-effective, easy, quick and more objective method used for provenancing of osseous material in forensic anthropological situations. Though this chemical forensic anthropological technique is still in its nascent phase and is to be accepted as a valid mean of establishing different components of identity, it is expected to have boundless applications in forensic as well as allied disciplines of inquiry in near future. There is a dearth of such techniques and instrumentation to be used in Indian scenario for forensic purposes, though it has been widely used for scrutinizing the quality of food products (water, milk, and honey), drug smuggling and other commercial purposes. Present review paper has highlighted the current status of use of stable isotopic analyses for forensic anthropological purposes.